Your human geography dissertation designing, doing, delivering - Peters, Kimberley A. (Thousand Oaks, CA SAGE Inc, 2017)
Guides students through the process of doing a human geography dissertation
Includes bibliographical references and index
Keywords: Dissertations, Academic; Human geography -- Authorship; Human geography -- Research; Literature; Human geography